2020
DOI: 10.1186/s13071-020-04367-w
|View full text |Cite
|
Sign up to set email alerts
|

Molluscicidal and parasiticidal activities of Eryngium triquetrum essential oil on Schistosoma mansoni and its intermediate snail host Biomphalaria glabrata, a double impact

Abstract: Background Freshwater snails are the intermediate hosts of a large variety of trematode flukes such as Schistosoma mansoni responsible for one of the most important parasitic diseases caused by helminths, affecting 67 million people worldwide. Recently, the WHO Global Vector Control Response 2017–2030 (GVCR) programme reinforced its message for safer molluscicides as part of required strategies to strengthen vector control worldwide. Here, we present the essential oil from Eryngium triquetrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Unlike the present study, Osman et al [ 65 ] showed that the fungal extract of Aspergillus fumigatus caused a higher mortality rate of miracidia than that of cercariae after exposure to the same experimental period. The mortality rates of both larval stages appear to differ depending on their biological nature and their internal structure [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the present study, Osman et al [ 65 ] showed that the fungal extract of Aspergillus fumigatus caused a higher mortality rate of miracidia than that of cercariae after exposure to the same experimental period. The mortality rates of both larval stages appear to differ depending on their biological nature and their internal structure [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide evidence that: (i) the ecotoxicological effect may vary between the target organisms; and (ii) the ecotoxicological action of the two plants studied goes beyond the action of their major component [8,31]. Together, these results are very interesting, especially with falcarinol and the oil of E. triquetrum, which can be used to support control strategies of parasitic diseases related to limnic environments.…”
Section: Ecotoxicity Activitymentioning
confidence: 67%
“…Some of them have traditionally been used for the treatment of various anti-inflammatory disorders and antinociceptive activity [6]. Secondary metabolites isolated from plants belonging to this genus have displayed important biological activities, including antitumor, antibacterial, molluscicide, parasiticide, antimicrobial, antifungal, cytotoxic and phototoxic [6][7][8][9][10]. Many studies deal with phytochemical constituents of the Eryngium genus, reporting terpenoids, polyacetylenes, triterpenoid, saponins, steroids and phenolics [6,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon probably occurred because the juvenile organism was not fully developed and was more susceptible to the effects of the nanoemulsion and essential oil components [15]. Several studies for the control of mollusks, especially B. glabrata and the parasite S. mansoni, have been conducted with products derived from plant origin, generating important information and showing the potential of plants as a source of bioactive metabolites to support the combat of schistosomiasis [5,7,29,[39][40][41][42][43]. However, few studies have approached the formulation of these novel natural products for the functional control of aquatic mollusks since the common limitation in these studies is the physicochemical properties of substances, which are often volatile or insoluble in aqueous media and generally require the use of organic solvents such as dimethyl sulfoxide (DMSO) to enable biological testing [29].…”
Section: Resultsmentioning
confidence: 99%